2006
DOI: 10.1016/j.stam.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

STM/STS study of superconducting diamond

Abstract: We present a scanning tunneling microscopy/spectroscopy (STM/STS) study of synthetic polycrystalline boron-doped diamond in the temperature range 0.5-4.3 K. At 4.3 K the sample-surface was very non-uniform and tunneling IðV Þ spectra were typical for p-type semiconductors. After cooling below the superconducting transition temperature, we detected and measured the superconducting gap of diamonds. At temperatures around 0.5 K the energy gap was around 0.8 and 1 mV (for two different samples).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(13 reference statements)
0
10
1
Order By: Relevance
“…We have checked that tunneling spectra did not depend on the tunnel resistance set point in the range 1 -10 M⍀. In contrast to early STM measurements on similar samples, 20,21 we observe in many locations an almost fully opened gap, presumably thanks to a better sample surface morphology. Within one grain, the electronic properties change smoothly as expected for a slow variation in doping concentration ͑small Fig.…”
contrasting
confidence: 99%
“…We have checked that tunneling spectra did not depend on the tunnel resistance set point in the range 1 -10 M⍀. In contrast to early STM measurements on similar samples, 20,21 we observe in many locations an almost fully opened gap, presumably thanks to a better sample surface morphology. Within one grain, the electronic properties change smoothly as expected for a slow variation in doping concentration ͑small Fig.…”
contrasting
confidence: 99%
“…We observed similar behavior for other pressure-synthesized samples. A superconducting energy gap was observed in diamond by means of STM in pressure-synthesized samples by Troyanovsky et al [9] and in single-crystalline CVD films by Sace´pe et al [10]. The latter authors were able to observe a triangular Abrikosov vortex lattice and to find a precise temperature dependence of the energy gap in the superconducting state of B-doped diamond.…”
Section: Resultsmentioning
confidence: 99%
“…Here we can also invoke some kind of Anderson's theorem and suggest that randomness gets renormalized to small values when we consider pairing among time-reversed states rather than Bloch states. The scanning tunnelling microscopy in superconducting boron doped diamond [26,27] does show strong spatial inhomogeneity in the order parameter, and at the same time, the system exhibits a robust bulk superconductivity. It has been suggested that the (singlet) valence bond maximization [28] holds the key to superconductivity.…”
Section: Mott Insulating Quantum Spin Liquid To a Superconductor Tranmentioning
confidence: 99%